Fuzzy inference system based 3D geographic routing in wireless sensor networks. (1st June 2019) - Shivappa, Nagesha; Manvi, Sunilkumar S.
Abstract : The 3D geographic routing in mobile wireless sensor networks (MWSNs) is gaining importance because of its simplicity, effectiveness, scalability and low cost. This study proposes a 3D geographic routing for multimedia traffic in MWSNs where the node which captures/senses an event establishes the route to the sink. If distance of an event node (source node) to the sink is within the sensing range, then the event data is transmitted to the sink. Otherwise, event node broadcasts bandwidth requirement to nodes. The surrounding nodes reply with bandwidth availability which is computed using fuzzy inference system situated in the node. The reply also comprises of node's residual energy and its distance to the sink. Event node identifies neighbour nodes which can provide the required bandwidth. The event node then selects the forwarder node from the list of neighbour nodes based on their residual energy and distance to the sink using another fuzzy inference system. The selected forwarder node becomes the source node and the process is repeated until one of the forwarder node finds the sink as neighbour. The algorithm is compared with dynamic 3D fuzzy routing based on traffic probability algorithm and novel fuzzy clustering scheme to demonstrate the improved performance.